2022
DOI: 10.3390/su14095457
|View full text |Cite
|
Sign up to set email alerts
|

Self-Determination as a Mechanism for Personality Sustainability in Conditions of Daily Stress

Abstract: During the COVID-19 pandemic, uncertainty, threat to life, and repeated lockdowns have significantly undermined people’s psychological well-being. In such situations, the basic needs for self-determination (SDT) are disrupted—autonomy, connectedness, and competence—but it is the resulting dissatisfaction that actualizes a search for strategies to cope with the problem. The objective of this article is to critically review the literature on various ways that people are coping with specific experiences during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 84 publications
0
5
0
1
Order By: Relevance
“…Studies at the end of the pandemic are characterized by location-based studies and small sample sizes. In contrast, a review of foreign studies showed a steady increase in surveys during the two years of the pandemic, some of which focused on the dynamics of coping strategies and others on their comparative analysis by age, country, and living conditions (Kostromina et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Studies at the end of the pandemic are characterized by location-based studies and small sample sizes. In contrast, a review of foreign studies showed a steady increase in surveys during the two years of the pandemic, some of which focused on the dynamics of coping strategies and others on their comparative analysis by age, country, and living conditions (Kostromina et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…The COVID-19 pandemic was a key event in 2020-2021 that had a significant impact on all aspects of people's lives around the world. The uncertainty of the situation, quarantine restrictions, and health concerns affected people's emotional states and psychological well-being and caused the need to find and form new patterns and strategies of behavior in a changed world (Chen et al, 2022;Sameer et al, 2020;Kostromina et al, 2022;Nestik et al, 2021;etc.). In the new circumstances, many people started to devote most of their time to watching films 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Комплементарная модель самодетерминации: уровневое описание В сущности, процессуальное понимание самодетерминации (Костромина, 2019;Москвичева и др., 2022;Kostromina et al, 2022) с точки зрения эволюции сложных открытых саморазвивающихся систем устраняет сложившееся противоречие в понимании самодетерминации как врожденного или приобретенного (социально обусловленного) свойства личности. Уровневое описание самодетерминации позволяет описать ее как комплементарную модель (рис.…”
Section: результатыunclassified